Does obesity in young women associated with disordered eating behaviors and mindful eating? - Bagcilar, Seliz; Gezer, Ceren (Progress in Nutrition, 2022)
Objective The onset of obesity has been associated with low levels of mindful eating and disordered eating behaviors. This study examined the relationship between mindful eating, disordered eating behavior and obesity in young women. Methods This cross-sectional study included 227 young women aged between 19-35 years. Mindful Eating Questionnaire (MEQ) and Eating Attitudes Test (EAT)-26 were used. Weight and body composition were obtained and the measurements of neck circumference (NC), waist circumference (WC), hip circumference (HC) were measured. Body mass index (BMI), waist-to-hip ratio (WHR) and waist-to-height ratio (WHtR) were calculated.Results Overall, the underweight participants had the highest MEQ scores, while the obese participants had the lowest MEQ scores (p